Collection of articles from rheology of ground and engineering geology - National Research Council of Canada. Institute for Research in Construction (National Research Council of Canada, 1987)
This document contains the translations of some recent articles written by Soviet scientists on the strength and creep of frozen soils, applicable to the design of foundations in permafrost areas. These will be of interest to anyone engaged in northern engineering work. Peer reviewed: No NRC publication: Yes